Pengaruh Digital Marketing dan Customer Relationship Marketing Terhadap Minat Berkunjung di Saung Angklung Udjo Bandung - Hadi Mulyana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
This research is aimed to discover the Digital Marketing and Customer Relationship Marketing of Visit Interest at Saung Angklung Udjo Bandung. It applies quantitative methode with the use of descriptive and verificative analysis as wel as the path linear regression analysis technique. The variable that has been used in the research is the digital marketing (X1), customer reletionship (X2) variable itself that hypothetically will lead to a positive and significant effect on the visit interest. The sample and population of research are 100 respondents off all tourist who visit in Saung Angklung Udjo Bandung. The testing instrument result shows that the hypothetic statement above is valid 0,30 and also reliable because it’s over 0,70. The descriptive analysis of digital (X1) variable, which is on the average of 4,0 falls into “good category”, the descriptive analysis customer relationship marketing (X2) variable, which is on average of 4,0 falls into “good category”. Meanwhile visit interest (Y) variable which is on the average of 4,1, fall into “good category”. The result of verificative analysis depects tcount 2,577 (X1), is higher than ttable which is 1,6608 and Fcount is inferred 32,623 higher than Ftable which is 3,94 so overall those variable show positive and significant result partially and simultaneously. The total of Digital Marketing and Customer Relationship Marketing of Visit Interest (R2) or the coefficient of determination is as high as 0,402 (40,2%), with the rest of 0,598 (59,8%) is affected by other factors that are not studied and covered by this research.